The Relationship Between Engine Exhaust Exposure And Risk of Cardiovascular Diseases Among Workers In Expressway Authority of Thailand - ทัพไทย ชนันพร; แก้วบุญชู อรวรรณ; บุณยมาลิก เพลินพิศ (Journal of The Royal Thai Army Nurses, 2019)
This study aimed to investigate the relationship between engine exhaust exposure and risk of cardiovascular disease among workers in Expressway Authority of Thailand. This research is a cross-sectional survey. Subjects were 177 expressway authority employees. Data were collected by questionnaire, an assessment of risk of cardiovascular disease was conducted by means of using the second derivative finger photo-plethysmogram (SDPTG). Relationships were analyzed using Pearson’s correlation coefficient and Multiple Regression Analysis The findings in this study indicated that SDPTG-AI was -0.51 ± 0.32, and exposure to car exhaust was found to be correlated with the risk of cardiovascular disease among workers in Expressway Authority of Thailand, which was statistically significant (r = 0.132 p-value = 0.035) after control of personal factors and health behaviors. Based on the results of this study, were the suggestions for the agencies to promote healthy behaviors such as weight control, sodium-controlled diet and Working behavior such as the use of personal protective equipment to reduce the risk of cardiovascular disease.